Peran Self-Efficacy dalam Pemahaman Matematis Peserta Didik: Tinjauan Sistematis terhadap Inkonsistensi Temuan Penelitian (2022–2025) - Ni Kadek Budi Liyastini; I Made Sugiarta; Kadek Ayu Mutiara Pratiwi; I Made Suarsana (Jurnal Prasasti Ilmu, 2026)
Mathematical understanding is a fundamental component of mathematics learning that enables students to comprehend concepts, connect mathematical representations, and apply mathematical ideas in various contexts. However, previous studies have indicated that students’ mathematical understanding remains relatively low across educational levels. This study aimed to systematically analyze the role of self-efficacy in students’ mathematical understanding and identify factors contributing to inconsistencies in previous findings. The study employed a Systematic Literature Review (SLR) based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were collected from the Scopus database by selecting studies published between 2022 and 2025 using relevant keywords related to self-efficacy and mathematical understanding. The PRISMA selection process resulted in nine articles that met the inclusion criteria. The selected studies were analyzed using qualitative thematic synthesis. The findings revealed that self-efficacy contributes positively to students’ mathematical understanding, both directly and indirectly through mediating variables such as learning motivation and self-regulated learning. Variations in findings were influenced by differences in research design, participant characteristics, educational level, and learning context. Experimental studies generally demonstrated stronger direct effects than correlational studies. Therefore, self-efficacy should be considered an important affective factor that needs to be strengthened alongside cognitive aspects in mathematics learning.